PENGARUH COSTUMER RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH DI PERUSAHAAN ASURANSI (KASUS AJB BUMI PUTERA 1912 CABANG SENAPELAN PEKANBARU) - Rhandy Pratama; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Competition that is increasingly sharply this claims company asurance that be able tomaintain and takes care of the client loyality. One of strategy needed to by the thing isstrategy Costumer Relationship Marketing. This research done to know influenceCostumer Relationship Marketing to Client Loyality. This research done to the clients byusing sampling pusphosive technique. Sample measure taken is 40. Data is collected bythrough interview by using questionaire and hereinafter processing data by usingdescriptive analysis and Kuantitative analysis. The result of a value of R Square, 0.78 or78% positively affect customer loyaltyResult of analysis indicates hat CostumerRelationship Marketing influential signifikan to Client Loyality.Key words: Costumer Relationship Marketing, Client Loyalty